Simulation of the Working Performance of a Shearer Cutting Coal Rock - Li-juan Zhao; Hong-mei Liu (Modelling and Simulation in Engineering)
Taking the MG2∗55/250-BWD shearer as the research object and considering the influence of the rock on the working performance of the shearer, the shearer-coal-rock coupled discrete element model was established and its dynamic working process has been studied. The single-factor analysis method was used to study the variation law of the cutting depth, traction speed, and the drum’s rotational speed on the three-way force acting on the drum, the coal loading rate, and the trajectory of the coal particles. The simulation showed that the coal loading rate fluctuated during the start-up phase of the shearer, and it was then constant as the time increased. The value of the cutting resistance was the largest, the traction resistance was the second largest, the axial force was the smallest, and the fluctuation coefficient of the axial force was the largest of all of them. The research showed that the coal loading rate of the drum decreased with the increase of the cutting depth, increased with the increase of the rotating speed of the drum, and decreased with the increase of the traction speed. The three-way force of the drum increased with the increase of the traction speed, decreased with the increase of the drum’s rotational speed, and increased with the increase of the cutting depth. According to the analysis of the coal cutting force and the coal loading rate, the drum could achieve high-efficiency cutting if the cutting depth, rotational speed, and traction speed of the dynamic were matched.